Acceptance and Commitment Therapy and the Dual Process Model of grief: a possible dialogue? - Freire, Anna Laura Leal; Vandenberghe, Luc (Perspectivas em Análise do Comportamento, 2025)
This article compares Acceptance and Commitment Therapy’s (ACT) application to grief with the Dual Process Model (DPM) of coping with bereavement. The method was a Grounded Theory oriented qualitative literature analysis. Both models promote the acceptance of emotions and the commitment to a meaningful life. DPM describes the oscillation between coping with loss and in restoration related stressors. It acknowledges both experiencing pain and the adaptive function of momentary escape. ACT emphasizes psychological flexibility and the deconstruction of experiential avoidance. It considers the dangers of fleeing from pain and proposes experiential exercises, metaphors and other tools to promote contact with the moment and commitment to values. We conclude the models are compatible and complementary. ACT therapists, when working with the bereaved, should incorporate awareness of the benefits of alternating between commitment and distraction. Therapists working with DPM should consider enriching their practice with ACT’s conceptual and clinical tools.